The Influence of Social Anxiety on Self-Compassion in Students Who Have Experienced Social Rejection - Nurul Hasanah; Nurul Dinni Octavia; Laila Hasyim (unprimdn.ac.id, 2026)
Experiences of social rejection in the school environment often trigger deep interpersonal anxiety in students, which in turn is predicted to erode their ability to treat themselves with compassion. Based on these considerations, this study aims to analyze the influence of social anxiety on self-compassion in students who have experienced social rejection. This study uses a quantitative approach with a simple linear regression method. The research sample consisted of 73 11th-grade students from SMA Negeri 2 Binjai, selected using purposive sampling from classes XI-3, XI-6, XI-8, and XI-10, with the criteria of having been identified as having experienced social rejection by peers at school. Data were collected using two psychological scales: a social anxiety scale adapting aspects from La Greca and Lopez, and a self-compassion scale developed based on aspects from Neff. The regression analysis results show a significant influence of social anxiety on student self-compassion (p = 0.000). The coefficient of determination (R Square) of 0.262 indicates that social anxiety contributes 26.2% to influencing students' self-compassion levels, while the remaining 73.8% is influenced by factors outside this research model. These findings emphasize the importance of developing guidance and counseling services that are responsive to students' emotional conditions to reduce social anxiety and restore their self-acceptance after rejection.